Genomic and Toxigenic Heterogeneity of Bacillus cereus sensu lato Isolated from Ready-to-Eat Foods and Powdered Milk in Day Care Centers in Colombia (2020)
ABSTRACT : Bacillus cereus sensu lato (s.l.) is a group of bacteria commonly found in diverse environments, including foods, with potential to cause emesis and diarrhea. In Colombia, it is one of the main foodborne pathogens. The aim of this study was to determine the genomic and toxigenic heterogeneity of B. cereus s.l. isolated from ready-to-eat foods and powdered milk collected in day care centers of Medellin, Colombia. Of 112 B. cereus s.l. isolates obtained, 94% were b-hemolytic. Toxigenic heterogeneity was established by the presence of nheABC, hblCDAB, cytK2, entFM, and cesB toxigenic genes. The nheABC operon and entFM gene were most frequently detected in the isolates, whereas the cesB gene was not found. According to the toxin genes content, nine toxigenic profiles were identified. A 44% of isolates had profiles with all genes for nonhemolytic enterotoxin, hemolysin BL, and enterotoxin FM production (profiles II and IV). Pulsed-field gel electrophoresis analysis indicated a high genomic heterogeneity among the B. cereus s.l., with 68 isolates grouping into 16 clusters and 33 placed separately in the dendrogram. This study provides useful information on the safety of ready-to-eat foods and powdered milk in day care centers where children, a susceptible population, are exposed and it should incentive for more studies to understand the distribution of different toxin-encoding genes among B. cereus s.l. isolates, enabling detailed risk assessment.